NASIONALISME DARI PERSPEKTIF FOUNDING FATHER (SEBUAH ANALISIS PSIKO-HERMENEUTIK) - Muhammad Zulfa Alfaruqy (Universitas Muhammadiyah Surakarta, 2022)
The purpose of research is to understand the meaning and dynamics of nationalism of a founding father, namely Ir. Soekarno. The research used qualitative methods with psycho-hermeneutic approaches. The research involved a single subject, Namely Ir. Soekarno. The results showed that nationalism contains consistent interactions between affective, cognitive, and conative. This is seen from the meaning of nationalism as a feeling of pride towards the group perceived as a nation-state on the basis of identity awareness that itself is a unified part of the group (in-group). Manifestations of nationalism in the form of political behavior create in-group unity and achieve independence from the domination of other nations (out-group). Meaning was gained through lifelong dynamics identified over four segments: partial, pre-integration, integration, and post-integration segments. Nationalism is an important element in the life of the nation and state. The soul of nationalist patrons, such as Ir. Soekarno, became relevant to be reread to be realized by all the nation's children.